Assessment of the dynamics of the development of the Russian labor market under the influence of the use of information and communication technologies - Sadovnikova, Natalia; Babich, Svetlana; Lebedinskaya, Olga (Nexo Revista Científica, 2022)
The article presents an assessment of the dynamics of the development of the Russian labor market in general and its technological component in particular. The article provides an assessment of the effectiveness of measures taken by the Government to stabilize the situation on the labor market. The authors identified regional differences in the labor market, presented the grouping of the subjects of the Russian Federation by the level of employment. The analysis confirms the hypothesis that significant changes have taken place in the Russian Federation in the scale of the use of information and communication technologies by enterprises and organizations, which, according to the authors, are caused by the complication of the economic situation of enterprises and organizations in certain types of economic activity.